2006
DOI: 10.1586/14737175.6.5.669
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of complex regional pain syndrome

Abstract: Complex regional pain syndrome (CRPS) most often follows injury to peripheral nerves or their endings in soft tissue. A combination of prostanoids, kinins and cytokines cause peripheral nociceptive sensitization. In time, the Mg(2+) block of the N-methyl-D-aspartate receptor is removed, pain transmission neurons (PTN) are altered by an influx of Ca(2+) that activates kinases for excitation and phosphatases for depression, activity-dependent plasticity that alters the firing of PTN. In time, these neurons under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 121 publications
(122 reference statements)
2
78
0
2
Order By: Relevance
“…Complex regional pain syndrome (CRPS) is a severe neuropathic pain condition characterized by persistent inflammation [12,19,30,54]. Our previous study demonstrated that circulating miRNAs in whole blood can be useful in stratification of patients with CRPS and that dysregulation of specific miRNAs correlates to symptoms and comorbidities associated with the disease [51].…”
Section: Introductionmentioning
confidence: 99%
“…Complex regional pain syndrome (CRPS) is a severe neuropathic pain condition characterized by persistent inflammation [12,19,30,54]. Our previous study demonstrated that circulating miRNAs in whole blood can be useful in stratification of patients with CRPS and that dysregulation of specific miRNAs correlates to symptoms and comorbidities associated with the disease [51].…”
Section: Introductionmentioning
confidence: 99%
“…However, this does not indicate that these genes are not involved in the initiation or maintenance of such conditions. The primary predictor of postoperative pain is the existence of pre-operative pain and even minor tissue injuries can apparently facilitate later injuries leading to pain pathologies16, 17, 28, 50. It is known that initial injury to sensory neurons leads to a significantly enhanced growth response to subsequent injuries22, 29, 36.…”
Section: Discussionmentioning
confidence: 99%
“…The broad spectrum of symptoms includes pain, inflammation, sensory dysfunction, impaired motor function, and trophic disturbances [1-4]. CRPS is subdivided into CRPS-I (reflex sympathetic dystrophy) and CRPS-II (causalgia), based on the absence or presence of documented nerve injury respectively [5].…”
Section: Introductionmentioning
confidence: 99%